2018
DOI: 10.3855/jidc.9805
|View full text |Cite
|
Sign up to set email alerts
|

The role of gender in the prevalence of human leptospirosis in Albania

Abstract: Introduction: Leptospirosis is a zoonotic spirochetal disease with global importance, which continues to have a major impact on public health in developing countries. The prevalence of the disease is much higher in males. The objectives of this study were: to give some data and to share our experience with human leptospirosis in Albania; to describe the prevalence regarding to the role of gender in the prevalence of human leptospirosis; to make a gender specific analysis of the clinical manifestations in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
(105 reference statements)
3
12
1
Order By: Relevance
“…The study was not in line with a study by Puca et al (2018), that obtained the highest prevalence of Leptospirosis was at the age of 45-69 years. The study revealed the characteristic similarities of age that it obtained almost similar percentages between case and control group.…”
Section: The Effect Of Age ≥ 20 To < 60 Years Old Toward Leptospirosis Incidencecontrasting
confidence: 95%
See 1 more Smart Citation
“…The study was not in line with a study by Puca et al (2018), that obtained the highest prevalence of Leptospirosis was at the age of 45-69 years. The study revealed the characteristic similarities of age that it obtained almost similar percentages between case and control group.…”
Section: The Effect Of Age ≥ 20 To < 60 Years Old Toward Leptospirosis Incidencecontrasting
confidence: 95%
“…In line with a study conducted by Lau and Jagals (2012), the study indicated that male was at risk in increasing leptospirosis incidences. Similar also with a study by Puca et al (2018), which also indicated that male was more at risk than female. It was related to their occupation.…”
Section: The Effect Of Sex Category (Female)supporting
confidence: 89%
“…Thus, most people with the disease have been involved in agriculture as their mainoccupation. [21][22][23] In many surveys, 17,18,24,25 including our study, leptospirosis was most common in middleaged people (40-60 years). In our patients, the mean hospitalization days were lower than in the study by Goris et al, 26 which could be due to the fact that in the study by Goris et al, 26 people with severe forms of the disease were examined.…”
Section: Discussionmentioning
confidence: 93%
“…The role of sex in the possibility of leptospirosis infection has been investigated in humans so that the prevalence of this disease in men is higher than that in women, possibly due to occupational exposure. 17,18 Leptospirosis is more common in temperate and tropical climates. 19 Pathogenic Leptospira can be found in ponds, rivers, pits, sewers, agricultural fields, and moist soils, 20 which is why agricultural occupations are so important in terms of occupational exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Leptospirosis is a microbial disease which affects both animals and humans in countries with tropical, humid and sub-tropical climates. It's also an occupational disease and also been found to be associated with the recreational activities, exposure through contaminated water or soil [1,2]. Humans and animals when they encounter a leptospirescontaminated environment become infected; entry is mainly through their skins and mucous membranes [2].…”
Section: Introductionmentioning
confidence: 99%